Apple polyphenols extract alleviated dextran sulfate sodium‐induced ulcerative colitis in C57BL/6 male mice by restoring bile acid metabolism disorder and gut microbiota dysbiosis. (20th November 2020) - Liu, Fang; Wang, Xinjing; Li, Deming; Cui, Yuan; Li, Xinli
Abstract : To investigate and compare the preventive effects of apple polyphenols extract (APE) with phloretin on dextran sulfate sodium (DSS)‐induced ulcerative colitis (UC), 60 male mice were treated with 125 or 500 mg/(kg bw d) APE or 100 mg/(kg bw d) phloretin, the single‐ingredient of APE, for continuous 3 weeks by intragastric administration, meanwhile, mice were provided with 3% DSS dissolved in drinking water to induce UC during the third week. Both APE and phloretin significantly ameliorated DSS‐induced UC by inhibiting body weight loss, preventing colon shortening and mucosa damage. Except the same mechanisms of the inhibited activation of NF‐κB signaling, decreased hyodeoxycholic acid level and increased abundance of Verrucomicrobia at phylum and Bacteroides and Akkermansia at genus, APE increased β‐muricholic acid level and decreased Bacterodetes abundance, while phloretin decreased Firmicutes abundance. Furthermore, APE treatment showed much lower disease activity index score, less body weight loss and lighter spleen than phloretin. Thus, our study supported the potentiality of APE as a promising dietary intervention for the prevention of experimental UC.